N-Iodosuccinimide-Promoted Selective Construction of Cyclopropyl and Dihydrofuranyl Spirooxindoles from Alkylidene Oxindoles and Annular β-Dicarbonyl Compounds - Chen, Hong; Xu, Hui; He, Zeng-Yang; Zou, Peng; Huang, Fei-Hong; Jin, Ying; Zhang, Ze (Synthesis, 2022)
An efficient N-iodosuccinimide-promoted cyclization of readily available alkylidene oxindoles with annular β-dicarbonyl compounds has been demonstrated. With five-membered cyclic β-dicarbonyl compounds as the starting materials, a series of cyclopropyl oxindoles can be obtained in good to excellent yields, whereas the method affords dihydrofuranyl spirooxindoles almost quantitatively when six- or seven-membered cyclic β-dicarbonyl compounds are employed. This protocol provides a new alternative to the practical synthesis of structurally diverse spirooxindoles.
Keywords: spirooxindoles; N-iodosuccinimide; β-dicarbonyl compounds; selective synthesis; cyclization